Method of assessment and predicting of influence on air pollution of technogenic urboecosystem - Кудрявська, Тетяна Борисівна; Дичко, Аліна Олегівна (Eastern-European Journal of Enterprise Technologies, 2014)
Disadvantages of the concept of maximum admissible concentrations call into question the reliability of modern methods for assessment and prediction of environmental conditions, so there is a need to develop new approaches. These approaches are based on the bioindication methods, as they are sensitive, reliable and sufficient for an adequate environmental assessment. The method of assessing the pollutant impact on the urboecosystem state was first introduced in the paper. It differs from the known by the fact that it uses biomonitoring data and considers environmentally admissible concentrations, defined on the basis of the determined dependence of abortiveness indicator of plant-bioindicator pollen on the pollutant concentration value for assessing the environmental condition. Also, the adequacy of this method was verified on the example of Kyiv. Environmentally admissible concentrations for significant abiotic factors and environmentally safe limits for relatively significant were determined. It is shown that existing standards exceed the values of environmentally admissible concentrations and environmentally safe limits by about 20 %.